(untitled) (Praxis Educativa, 2026)
In a context characterised by deepening injustices and inequalities, this article puts forward the idea of rethinking educational research as a relational and affective practice. Using String Play as both a methodological approach and an analytical framework, and engaging with agentic realism and posthumanist perspectives, the article explores alternative modes of knowledge production that transcend dichotomous and anthropocentric categories. This methodological approach is based on gestures created during an investigation into everyday school life in exclusionary contexts, which is linked to the author’s doctoral dissertation. The research involves creating string figures with other bodies — both human and non-human — thereby repositioning the researcher as a constitutive part of the narrative being studied. The result is an affective narrative that recounts the tensions, intensities and movements involved in holding the strings, revealing a way of conducting research as an embodied practice in a constant process of becoming with others.